Liver-expressed antimicrobial peptide 2 is a hepatokine regulated by ghrelin, nutrients, and body weight - Islam, Md Nurul; Nabekura, Hiroki; Ueno, Hiroaki; Nishida, Takahiro; Nanashima, Atsushi; Sakoda, Hideyuki; Zhang, Weidong; Nakazato, Masamitsu (Scientific reports, 2024)
Liver-expressed antimicrobial peptide 2 (LEAP2) is a peptide that counteracts the hunger hormone ghrelin-induced functions. Recently, we showed that vertical sleeve gastrectomy (VSG) did not alter the serum LEAP2 concentration in individuals with obesity. Here, we investigated the effects of VSG in both chow diet (CD)-fed and high-fat diet (HFD)-fed mice. In CD-fed mice, VSG increased plasma LEAP2 levels and hepatic Leap2 mRNA levels while decreasing body weight, blood glucose levels, and ghrelin levels. Intraperitoneal (ip) administration of ghrelin reversed these changes. These effects were found in both male and female mice. In contrast, VSG or weight loss in HFD-induced obese mice decreased LEAP2 levels. After fasting, the plasma LEAP2 concentration was in the following order: hepatic vein > abdominal aorta > portal vein. A high glucose concentration robustly increased the plasma LEAP2 concentration in the hepatic vein and abdominal aorta but not in the portal vein. In addition, corn oil or palmitate increased LEAP2 expression and secretion. The increase in LEAP2 levels after the meal tolerance test was delayed in the human subjects with diabetes. Our data suggest that various factors (metabolic, hormonal, and nutritional) regulate LEAP2, and the liver is the predominant site for the production and secretion of LEAP2. Furthermore, the interaction between ghrelin and LEAP2 is involved in the pathogenesis of obesity and diabetes.